A Optimalisasi Strategi Penanganan Sindrom Pramenstruasi: Studi Kasus di Desa Larangan RT.15 RW. 04 Sidoarjo - Purwanti, Yanik; Adawiyah, Robbiatul; Wisaksono, Arief (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
A set of physical symptoms that usually appear a few days to a week before menstruation and disappear after menstruation is known as Premenstrual Syndrome (PMS). Of the 10 young women involved in the research, 8 (80%) of them had experienced premenstrual syndrome, according to survey data conducted in Larangan Village, Sidoarjo. This high incidence rate shows that premenstrual syndrome is still a health problem for young women in this village. The aim of this research is to get an idea of what young women know about premenstrual syndrome and how to treat it. This research used a descriptive survey method involving all young women (15 people) in Larangan Village RT 15/RW 04. The variables observed included knowledge about premenstrual syndrome and the treatment used. To collect data, Google Form was used to distribute questionnaires online. The results showed that the majority (53.3%) of young women had sufficient knowledge about premenstrual syndrome. In addition, most of them (73.3%) carried out treatment when experiencing premenstrual syndrome, and more adolescent girls who underwent treatment (83.3%) showed less knowledge, while more adolescent girls who did not undergo treatment (37 .7%) indicates sufficient knowledge. These results indicate that efforts need to be made to increase adolescent girls' understanding of premenstrual syndrome and how to treat it to reduce the negative effects of incorrect treatment practices. Keywords: Knowledge, Treatment, Young Women, Premenstrual Syndrome